Effect of Cognitive Task on Gait Balance in People With Functional Ankle Instability - Saeed Forghany; Sanam Tavakoli Oskoei (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Some individuals with Chronic Ankle Instability (CAI) termed as functional ankle instability (FAI) suffer from repetitive ankle giving way and feeling of ankle joint instability during dynamic activities like walking. Walking, as a postural task, requires some central attention to integrate sensory inputs, estimate, and plan and produce proper motor outputs. Attention demanding cognitive task has the ability to influence walking control and may increase the risk of giving way and ankle sprain. The purpose of this study was to investigate the effect of dual-tasking on dynamic balance in people with FAI. Materials & Methods Twelve physically active with clinically diagnosed FAI and 12 matched controls completed trials of normal walking in isolation or with a concurrent cognitive task, which is repeatedly subtracting seven from a randomly selected number (between 200 and 250) and the same cognitive task while sitting. Spatiotemporal parameters (measured by a seven-camera motion capture system) were calculated by visual3D during gait cycles. Gait velocity, step time, step length, stance time, and swing time were calculated. Independent t-test was used to compare the data for FAI and control groups, and comparisons between the single and dual task conditions were made using the paired t-test. Step time variability was calculated using Intraclass Correlation (ICC). Results The results indicated that step velocity was decreased and that stance, swing, and step time were increased significantly during dual task walking in FAI people (P<0.05). FAI people demonstrated greater step time variability during single and dual tasks compared to the control group.  Conclusion The athletes with FAI demonstrated different movement strategies during the dual-task condition compared to control group. Cognitive load may increase the risk of ankle instability in individuals with FAI.